A method for preparing bimetallic nanoparticles from zero-valent metal precursors

By using a zero-valent metal precursor and another metal compound to heat treatment on the support, bimetallic nanoparticles with narrow particle size distribution were prepared, which solved the problem of insufficient activity and selectivity of bimetallic nanoparticles in the prior art, and achieved significant improvement in the catalysis field.

CN116173981BActive Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111419902.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-26
Publication Date
2025-03-18
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

It is difficult to prepare bimetallic nanoparticles with high activity, specific morphology and narrow particle size distribution in the prior art. Especially in the application in the field of catalysis, the activity and selectivity of a single metal catalyst are insufficient.

Method used

A zero-valent metal precursor is used to react with another metal compound in solution, and bimetallic nanoparticles with narrow particle size distribution are formed on the support by heat treatment. The specific steps include mixing the zero-valent metal precursor with another metal compound, loading it onto a solid support, and performing heat treatment in solution.

Benefits of technology

High activity and selectivity of bimetallic nanoparticles were achieved, especially in the preparation of furfurol reaction with selective hydrogenation of furfural, which showed nearly 100% selectivity and significantly improved activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116173981B_ABST
    Figure CN116173981B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing bimetallic nanoparticles from a zero-valent metal precursor. Another metal compound is added to a zero-valent metal precursor solution having a weak coordination environment and protected by an ether structure compound and hydrogen chloride to obtain a bimetallic solution. The solution is loaded onto a carrier and subjected to heat treatment in the solution to obtain loaded bimetallic nanoparticles. The preparation conditions of the bimetallic nanoparticles are mild and the particle size distribution is narrow, which provides guidance for preparing loaded bimetallic nanoparticles with low loading, high activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of technical inventions, and specifically relates to a method for preparing bimetallic nanoparticles from zero-valent metal precursors. Background Art

[0002] Chemical reactions are the basis of human survival and social development. The use of catalysts is a necessary means to improve the rate of chemical reactions and product selectivity. The development of efficient catalysts is one of the important research contents in the field of catalysis (Journal of Materials Chemistry A, 2019, 7, 3492-3515). Metal catalysts are one of the earliest catalysts used in industry. In order to efficiently utilize metals and save costs, most of the metal catalysts currently used in industry are supported metal catalysts. Metals are loaded on carriers in the form of nanoparticles or clusters, and have unique optical, electronic and magnetic properties, which are different from the properties of bulk metals (Chem. Soc. Rev., 2012, 41, 8099). Designing and synthesizing nanoparticles with high activity, specific morphology and narrow particle size distribution, and applying them in catalysis, magnetic devices, gas sensing, biodiagnosis and other fields are of great significance and challenge (Chem. Lett., 1987, 405–408; Chem. Rev. 2005, 105, 1547; Chem. Rev. 2004, 104, 3893).

[0003] With the rapid development of characterization technology, not only single metal nanoparticles have been deeply studied, but also bimetallic nanoparticles have received extensive attention. Bimetallic nanoparticles are composed of two metal components, and the synergistic effect between the two components makes bimetallic nanoparticles exhibit unique properties different from their single metal components. Therefore, bimetallic nanoparticles have a wide range of applications in the field of catalysis, such as oxidation reactions (Chem. Soc. Rev., 2008, 37, 1619–1628), hydrogenation reactions (Angew. Chem., Int. Ed., 2001, 40, 1211–1215), hydrogenolysis reactions (Angew. Chem., Int. Ed., 2012, 51, 2564–2601), etc. They have high activity, selectivity and stability. These reactions are not only important reactions in the traditional field of petroleum refining, but also important reactions in the preparation of fuels and chemicals from renewable energy-biomass refining.

[0004] The preparation method of bimetallic nanoparticles can refer to the preparation of single metal nanoparticles. They can be prepared in gas phase, liquid phase or solid matrix. However, since they have two metal components, their controllable preparation is more complicated. Traditional preparation methods of bimetallic nanoparticles include chemical reduction, thermal decomposition of suitable precursors, electrochemical synthesis and sonochemical methods (Chem. Soc. Rev., 2012, 41, 8099–8139). Since the preparation method has an important influence on the morphology and composition distribution of bimetallic nanoparticles, and thus affects their properties. Therefore, it is of great significance to design a bimetallic nanoparticle with simple and mild preparation conditions, high activity and stability, and narrow particle size distribution.

[0005] Zhang et al. (Nat. Commun. 2019, 10, 996; CN201611004958.3) prepared a zero-valent mononuclear platinum atom (R1OR2)2Pt(0)Cl2H2 protected by polyethylene glycol-based polydimethylsiloxane in solution, which is weakly coordinated with two molecules of hydrogen chloride and two oxygens. Furthermore, by replacing the protective agent with different oxygen-containing species (chain ether compounds), mononuclear platinum atoms with smaller coordination groups and easy removal of excess protective agents were synthesized (ChemNanoMat. 2020, 6, 1-10; CN201910096696.5). The ligand steric hindrance of the mononuclear platinum atom protected by this chain ether compound is low, and the coordination ability with the metal platinum center is weak and easy to leave, which provides the possibility for the controllable preparation of metal materials as a precursor.

[0006] The present invention uses a zero-valent metal as a precursor, adds another metal compound to its solution, and then loads it onto a carrier. Finally, by heat treatment in the solution, bimetallic nanoparticles with a narrow particle size distribution and high dispersion on the carrier are obtained. The bimetallic platinum-cobalt nanoparticles are applied to the reaction of furfural selective hydrogenation to prepare furfural alcohol. When furfural is fully converted, it shows a furfural alcohol selectivity of nearly 100%. Compared with a single metal platinum component, the activity and selectivity are greatly improved. At the same time, it is found that another metal component plays the role of a protective agent, which provides guidance for the preparation of high-activity, high-stability and high-load precious metal catalysts. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing bimetallic nanoparticles from zero-valent metal precursors.

[0008] The zero-valent metal precursor is composed of a protective agent ether compound, hydrogen chloride and a metal center. Another metal compound is added to the solution containing the zero-valent metal precursor to obtain a bimetallic solution. The solution is loaded onto a solid carrier and heat-treated in the solution to obtain loaded bimetallic nanoparticles.

[0009] The other metal compound added to the solution containing the zero-valent metal precursor includes transition metals and platinum group elements, including but not limited to one or more of vanadium, manganese, iron, cobalt, nickel, copper, zinc, tin, ruthenium, rhodium, palladium, osmium, iridium, gold, and silver.

[0010] The other metal precursor includes one or more of metal chlorides, nitrates, carbonates, and metal carbonyl compounds.

[0011] The other metal precursor includes but is not limited to one or more of ferric chloride, cobalt chloride, tin chloride, vanadium chloride, ruthenium chloride, palladium chloride, iridium chloride, ferric nitrate, cobalt nitrate, nickel nitrate, dicobalt octacarbonyl, rhodium carbonyl, ruthenium carbonyl, cobalt acetylacetonate, and ferric acetylacetonate.

[0012] The solution used in the pyrolysis process includes but is not limited to alcohol compounds, which are one or more of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, and ethylene glycol diethyl ether.

[0013] The gas atmosphere of the heat treatment process includes but is not limited to one or more of hydrogen, nitrogen, argon, helium and oxygen.

[0014] The temperature range of the decomposition process is 0-200°C, preferably 60°C.

[0015] The zero-valent metal precursor comprises one or more of platinum group elements and post-platinum group elements, including but not limited to one or more of palladium, rhodium, iridium, ruthenium, osmium, platinum and gold, preferably a zero-valent platinum precursor.

[0016] The protective agent includes but is not limited to one or more ether structural compounds; the protective agent includes but is not limited to one or more block copolymers of siloxy groups and polyether groups, macrocyclic polyethers and chain ether compounds; preferably includes but is not limited to one or more polysiloxane-polyglycol compounds, crown ethers and glycol ether structural compounds.

[0017] The protective agent ether compound includes, but is not limited to, one or more of polysiloxane-polyethylene glycol block copolymer, 15-crown-5 ether, ethylene glycol dimethyl ether, and ethylene glycol diethyl ether.

[0018] The bimetallic platinum-cobalt nanoparticles were used to catalyze the selective hydrogenation of furfural to furfuryl alcohol, and they showed significantly higher activity and selectivity than single metal nanoparticles. The preparation conditions of the bimetallic nanoparticles were mild, and the particle size distribution was narrow, which provided guidance for the preparation of supported bimetallic nanoparticles with low loading, high activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the CO adsorption infrared spectrum of the monodisperse bimetallic platinum-cobalt material supported by titanium dioxide in Example 2.

[0020] Figure 2 This is the CO adsorption infrared spectrum of the bimetallic platinum-cobalt nanoparticles supported on titanium dioxide in Example 3.

[0021] Figure 3 This is the TEM image of bimetallic platinum-cobalt nanoparticles supported on titanium dioxide in Example 3.

[0022] Figure 4 This is the particle size distribution diagram of the bimetallic platinum-cobalt nanoparticles supported on titanium dioxide in Example 3.

[0023] Figure 5 This is the area of ​​line scan and electron energy loss spectroscopy analysis of bimetallic platinum-cobalt nanoparticles supported on titanium dioxide in Example 3.

[0024] Figure 6 Example 3 Titanium dioxide supported bimetallic platinum cobalt nanoparticles Figure 5 Line scan image of the area.

[0025] Figure 7 Example 3 Titanium dioxide supported bimetallic platinum cobalt nanoparticles Figure 5 Electron energy loss spectrum of the region.

[0026] Figure 8 This is Example 4, the catalytic performance of bimetallic platinum-cobalt nanoparticles supported on titanium dioxide in catalyzing the hydrogenation of furfural to produce furfuryl alcohol. DETAILED DESCRIPTION

[0027] The invention is further described in detail below by taking the preparation of bimetallic PtCo nanoparticles on a TiO2 carrier as an example. The protection content of this patent is not limited to the specific implementation method, but is limited by the claims.

[0028] Example 1

[0029] Preparation of binuclear platinum-cobalt precursor solution: 67.5 ml of ethylene glycol diethyl ether, 67.5 ml of ethanol, 10.2 ml of ultrapure water and 4.8 ml of 0.018 mol / L chloroplatinic acid solution were fully mixed, then heated, condensed and refluxed at 82 °C for 2 hours to completely reduce the chloroplatinic acid to obtain a zero-valent platinum precursor solution (CN201910096696.5).

[0030] In a glove box, weigh 15 mg of dicobalt octacarbonyl and put it into a three-necked flask, and then introduce nitrogen into the three-necked flask. Transfer the zero-valent platinum precursor solution that has been bubbled with nitrogen for 1 hour to the three-necked flask containing dicobalt octacarbonyl. Condensate and reflux at 60°C for 3 hours, then cool to room temperature for use.

[0031] Example 2

[0032] Preparation of monodisperse binuclear platinum-cobalt material loaded with titanium dioxide: 100 ml of binuclear platinum-cobalt precursor solution in Example 1 was taken, first concentrated to 20 ml, and 2.263 g of TiO2 (anatase) was added and fully impregnated for 24 hours. Ethanol and ethylene glycol diethyl ether were removed by vacuum distillation at 40°C, and vacuum dried at 40°C for 12 hours to obtain a monodisperse platinum-cobalt-titanium dioxide material with a mass loading of 0.5%. The infrared spectrum of CO adsorption on this monodisperse material ( Figure 1 ) shows that platinum is dispersed on titanium dioxide in the form of single atoms. (Note: 2105cm -1 The peak at 1800-1900cm is the linear adsorption peak of CO on platinum single atom. -1 The bridge adsorption peak of CO on Pt nanoparticles is between 2105cm -1 The CO adsorption peak position at 240 nm did not undergo a blue shift, which indicates that platinum exists in the form of a single atom.

[0033] Example 3

[0034] Preparation of titanium dioxide-supported bimetallic platinum-cobalt nanoparticles: 20 mg of the monodispersed binuclear platinum-cobalt material supported by titanium dioxide in Example 2 was transferred to a 15 ml quartz tube liner, 4 ml of isopropanol was added, 1 MPaH2 was introduced at room temperature, and after treatment at 60°C for 2 h, the bimetallic platinum-cobalt nanoparticles supported by titanium dioxide were obtained by washing and drying. The material was characterized by CO adsorption infrared ( Figure 2 ) shows that CO is at 2105cm -1 The signal at 2063 cm and 1836 cm -1 The signals of 2 and 10 cm are respectively attributed to the linear adsorption and bridge adsorption of CO on Pt nanoparticles, indicating that the monodispersed Pt has been completely decomposed into nanoparticles. -1 A shoulder peak appears at , which is attributed to the adsorption of CO on cobalt with partial positive charge. Figure 3 ) It can be seen that the bimetallic platinum-cobalt nanoparticles have good dispersion on titanium dioxide, and the particle size distribution is narrow between 1-5nm ( Figure 4 ), with an average particle size of 2.1 nm. Moreover, the addition of cobalt did not affect the platinum lattice, indicating that cobalt may be located on the surface of the platinum particles. EDX line scanning mode ( Figure 6 ) shows that the signal strength trends of cobalt and platinum are consistent, indicating that cobalt is evenly distributed on platinum. In addition, the electron energy loss spectrum on platinum particles ( Figure 7 )The cobalt signal appears, which further proves that Co is dispersed on the Pt particles.

[0035] Example 4

[0036] Preparation of furfuryl alcohol by hydrogenation of furfural catalyzed by bimetallic platinum-cobalt nanoparticles: 20 mg of the bimetallic platinum-cobalt nanoparticles supported by titanium dioxide in Example 3 were added with 4 ml of isopropanol and 50 mg of furfural, 1 MPa of H2 was introduced at room temperature, and the reaction was carried out at 30°C for 5 h at a speed of 350 rpm. The gas chromatography analysis results ( Figure 8 ) It can be seen that the bimetallic platinum-cobalt nanoparticles have nearly 100% furfural conversion and nearly 100% furfuryl alcohol selectivity. Compared with single metal platinum or cobalt, bimetallic platinum-cobalt particles greatly improve the activity and selectivity of the reaction.

[0037] From the above examples, it can be seen that bimetallic platinum-cobalt nanoparticles with an average particle size of 2.1 nm were prepared on titanium dioxide by adding cobalt compounds from a zero-valent platinum precursor, which were well dispersed on titanium dioxide, and cobalt was evenly distributed on the surface of the platinum particles. Further studies have found that the bimetallic platinum-cobalt nanoparticles have significantly higher activity and selectivity than single metals in the reaction of furfural hydrogenation to furfuryl alcohol.

Claims

1. A method for preparing bimetallic nanoparticles from a zero-valent metal precursor, characterized in that: 1) Zero-valent metal precursor solution: Disperse the zero-valent metal precursor in a solution of ether compound, ethanol and water; 2) adding another metal compound to a solution containing a zero-valent metal precursor to obtain a bimetallic solution; 3) loading the bimetallic solution onto a solid carrier and heat treating the solution to obtain loaded bimetallic nanoparticles; The zero-valent metal precursor is a zero-valent platinum precursor, The metal compound is dicobalt octacarbonyl, and the molar ratio of dicobalt octacarbonyl to zero-valent platinum is 0.5-10, and the total mass loading of the bimetal on the carrier is 0.1-5 wt. %.

2. The method according to claim 1, characterized in that: The molar ratio of the metal compound to zero-valent platinum is 0.5-2; the total mass loading of the bimetal on the carrier is 0.5-2 wt. %.

3. The method according to claim 1, characterized in that: The solution used in the heat treatment process of step 3) is one or more of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, and ethylene glycol diethyl ether.

4. The method according to claim 1 or 3, characterized in that: The gas atmosphere of the heat treatment process is one or more of hydrogen, nitrogen, argon, helium and oxygen.

5. The method according to claim 1 or 3, characterized in that: The temperature range of the heat treatment process is 20-200° C. and the time is 1-4 hours.

6. The method according to claim 5, characterized in that: The temperature range of the heat treatment process is 60-140° C. and the time is 2 hours.

7. The method according to claim 1, characterized in that: The concentration of the zero-valent platinum precursor in the solution is 0.58 mmol / L.

8. The method according to claim 1, characterized in that: The ether compound is one or more of macrocyclic polyether and chain ether compounds.

9. The method according to claim 1, characterized in that: The ether compound is one or more of crown ether and glycol ether structural compounds.

10. The method according to claim 1 or 9, characterized in that: The ether compound is one or more of 15-crown-5 ether, ethylene glycol dimethyl ether and ethylene glycol diethyl ether.

Citation Information

Patent Citations

  • A noble metal lone atom material stable in solution

    CN108067631B

  • A solution-stable reduced-state noble metal lone atom material and its preparation method

    CN111496265B

  • Precious metal isolated atomic material being stable in solution

    CN108067631A

  • Bimetallic catalyst for preparing furfuryl alcohol by furfural selective hydrogenation and preparation method and application thereof

    CN110193370A

  • Reduction state noble metal isolated atom material stable in solution and preparation method thereof

    CN111496265A